2022
DOI: 10.2196/31634
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Web-Based and In-Person Educational Workshops for Canadian Occupational Therapists and Understanding Their Learning Experiences: Mixed Methods Study

Abstract: Background The Do-Live-Well (DLW) framework is an occupation-focused health promotion approach. Occupational therapists (OTs) have been interested in training opportunities regarding this framework. Traditionally, in-person continuing educational interventions are the main way that OTs obtain knowledge, but web-based learning has become popular among health care professionals. However, its effectiveness and learners’ experience in web-based learning have not been well-studied in occupational therap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…In a study comparing the differences in virtual versus in-person training for occupational therapists, researchers found that while knowledge acquisition did not differ between the two groups, participant’s satisfaction rating was higher for the in-person group than for the web-based group owing to lack of in-person interactions, lack of ease in networking, and synchronous interactions in the web-based setting. The same study also found that participants appreciated the ease of accessibility and flexibility provided by the web-based learning modules [ 6 ]. Another study assessing the development of empathy in premedical students found a significant increase after a 2-week remote learning course.…”
Section: Introductionmentioning
confidence: 98%
“…In a study comparing the differences in virtual versus in-person training for occupational therapists, researchers found that while knowledge acquisition did not differ between the two groups, participant’s satisfaction rating was higher for the in-person group than for the web-based group owing to lack of in-person interactions, lack of ease in networking, and synchronous interactions in the web-based setting. The same study also found that participants appreciated the ease of accessibility and flexibility provided by the web-based learning modules [ 6 ]. Another study assessing the development of empathy in premedical students found a significant increase after a 2-week remote learning course.…”
Section: Introductionmentioning
confidence: 98%
“…It also reduced time expenditure and costs, in contrast to in-person training, which had to be repeated at each crossover point [ 22 ]. However, our intervention overcame the disadvantages of web-based learning (mainly isolation) [ 23 - 25 ] with the in-person part of the training, which provided role play, feedback, and discussion opportunities for applying knowledge to skills and behavior [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies that included procedural knowledge components addressed theories, frames of reference [26,27], adaptive equipment [28], psychosocial dysfunction [29], communication partner training for adult aphasia [30], and interprofessional team skills [31]. Studies involving both procedural knowledge and professional reasoning addressed ergonomics, autonomy, activity analysis, and other OT subjects [32], adult practice [33], mental health [34], fieldwork training [35], interprofessional team skills in childhood, school practice [36], dolive-well framework [37], and problem-based learning (OTA:) scenarios [38]. In addition, the studies included only professional reasoning elements and provided casebased professional reasoning training, such as sensory processing and occupational performance process model (OPPM) application of cases [39][40][41] (Table 1).…”
Section: Key Clinical Skills Subjects and Outcomesmentioning
confidence: 99%